2013
DOI: 10.3109/14767058.2013.783803
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Bartter syndrome and unilateral ectopic renal cyst as new renal causes of hydrops fetalis: two case reports and review of the literature

Abstract: Non-immune hydrops fetalis (NIHF) is a challenging entity as it represents the end stage of several different disorders. Renal and genitourinary causes of NIHF are rare and include congenital renal malformations, tumors and ureter-urethra disorders. Herein, two NIHF cases with different renal causes were presented. The first case that had antenatal NIHF was diagnosed neonatal Bartter syndrome. The second case of NIHF with antenatal large cyst in the surrenal gland area required surgery and ectopic renal cyst w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For the included case series ( Supplementary Figure S2 ), the quality assessment of the included studies identified two studies [ 59 , 61 ] as high quality, six studies [ 58 , 62 , 63 , 64 , 65 , 66 ] as medium quality, and one study [ 60 ] as low quality. Only five [ 59 , 61 , 62 , 64 , 66 ] studies gave clear criteria for inclusion in the case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the included case series ( Supplementary Figure S2 ), the quality assessment of the included studies identified two studies [ 59 , 61 ] as high quality, six studies [ 58 , 62 , 63 , 64 , 65 , 66 ] as medium quality, and one study [ 60 ] as low quality. Only five [ 59 , 61 , 62 , 64 , 66 ] studies gave clear criteria for inclusion in the case series.…”
Section: Resultsmentioning
confidence: 99%
“…Only five [ 59 , 61 , 62 , 64 , 66 ] studies gave clear criteria for inclusion in the case series. The condition was not measured in a standard, reliable way for the included participants in two studies [ 60 , 63 ]. All of the studies used a valid method for the identification of the condition.…”
Section: Resultsmentioning
confidence: 99%
“…Fraser syndrome may present with renal agenesis and NIHF . NIHF has been described in association with Bartter syndrome, in which renal cysts may be seen prenatally. Finally, enlarged, multicystic kidneys have been reported with NIHF in the setting of both Meckel Gruber syndrome and infantile polycystic kidney disease .…”
Section: Genetic Causes Of Nihf By Organ Systemmentioning
confidence: 99%
“…Urorectal septum malformation sequence (URSMS) leading to meconium peritonitis and non-immune fetal hydrops was first reported in 2006 [166]. Subsequently multiple papers looking at the aetiology of all fetal hydrops cases attribute a small percentage (2-3%) to 'urogenital malformations', including prune-belly syndrome, renal agenesis, neonatal Bartter syndrome and cystic kidney disease [2,72,[167][168][169]. Still, non-immune fetal hydrops is an unusual presentation of urogenital tract malformations.…”
Section: Urogenital Malformationmentioning
confidence: 99%